Pengaruh krisis keuangan global terhadap indeks harga saham gabungan regional asia dan bisnis di indonesia - Daryatno, Andreas Bambang; Ramli, Ishak (Jurnal Ekonomi, 2013)
Results of analysis of research data proving that the global financial crisis is significantly affecting the Asia Regional Stock Price Index and the Asia Regional Stock Price Index significantly affect business activities in Indonesia, but the global financial crisis did not significantly affect business activities in Indonesia and simultaneous Global Financial Crisis and the Asia Regional Stock Price Index did not significantly affect the Business activities in Indonesia. This means that business activities in Indonesia are more influenced by the Regional Asia Stock Price Index compared to the direct impact of the global financial crisis. Data analysis tool using the Structural Equation Model (SEM) using Lisrel Software 8.8. Observations were made at the end of each month from January 2004 until June 2010. This study used an exogenous latent variable (the Global Financial Crisis) and two endogenous latent variables (namely JCI Asia Regional and Business in Indonesia). The Global Financial Crisis is measured by two indicator variables namely World Inflation and the Stock Market U.S. Index. JCI Asia Regional measured by four indicator variables namely the China Stock Price Index (Shanghai), Japan Stock Price Index (Nikkei), South Korea Stock Price Index (Kospi), and India Stock Price Index (Bombay), whereas Business in Indonesia is measured by two indicator variables namely the Indonesia Stock Price Index (BEI) and Indonesia's inflation.